2014
DOI: 10.1111/pan.12420
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for preventing side effects of systemic opioid in postoperative pediatric patients

Abstract: Data from 62 studies were reviewed. The strategies that could effectively prevent and reduce opioid side effects in pediatric patients during the postoperative period included minimizing the amount of opioid consumption by a multimodal approach, opioid titration, using local anesthetic techniques and providing the specific prophylaxis for each side effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 64 publications
2
58
1
4
Order By: Relevance
“…4 In pediatric patients, aggressive and proactive pain management is recommended perioperatively 5 ; however, because of opioid-related adverse effects, strategies minimizing the amount of opioid consumption are required. 6 Regional anesthesia with ultrasound guidance, such as peripheral nerve blocks 7 that can be placed safely under general anesthesia or deep sedation, 8 is increasingly used in pediatric patients. Therefore, surgical site-specific peripheral regional anesthesia was considered for treating post-USRM pain.…”
mentioning
confidence: 99%
“…4 In pediatric patients, aggressive and proactive pain management is recommended perioperatively 5 ; however, because of opioid-related adverse effects, strategies minimizing the amount of opioid consumption are required. 6 Regional anesthesia with ultrasound guidance, such as peripheral nerve blocks 7 that can be placed safely under general anesthesia or deep sedation, 8 is increasingly used in pediatric patients. Therefore, surgical site-specific peripheral regional anesthesia was considered for treating post-USRM pain.…”
mentioning
confidence: 99%
“…Thus, it is meaningful for the reduction of opioid analgesics consumption in children. Some researchers have suggested that minimizing the dose of opioid analgesics could reduce the side effects (30). The previous meta-analyses in adult have demonstrated the significant reduction of opioid usage in regional anesthesia treated adults group while comparing with placebo treated group, and the side effect of opioids such as nausea, sedation, and pruritus were reduced due to the lower opioid consumption (14,31,32).…”
Section: Discussionmentioning
confidence: 95%
“…A wide range of drugs have been associated with central emetic side effects and secondary effects due to gastric irritation [ 8 ]. Among the drugs with central emetic effects are opiate analgesics [ 85 ] and chemotherapeutics agents [ 86 ]. Other drugs can induce vomiting secondary to gastric irritation, such as aspirin, diuretics, and alcohol [ 5 ].…”
Section: Side Effect Of Drugsmentioning
confidence: 99%